POWER, DEMOCRACY, AND INSTITUTIONAL REFORM: A SYSTEMATIC LITERATURE REVIEW OF INDONESIAN POLITICAL DYNAMICS - Khairunnisah Lubis (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2026)
Indonesian politics has undergone transformative shifts since the fall of Suharto's New Order regime in 1998, ushering in an era of democratic consolidation marked by multiparty competition, direct elections, and sweeping decentralization. This study employs a systematic literature review (SLR) methodology to synthesize and critically analyze scholarly works published between 2000 and 2024 on the key dimensions of Indonesian political dynamics, including democratization trajectories, executive-legislative relations, the role of political parties, decentralization and regional autonomy, and the challenges of institutional reform. Drawing from peer-reviewed journal articles, books, dissertations, and policy documents sourced from Google Scholar, JSTOR, Scopus, and national repositories, this review identifies persistent structural tensions in Indonesia's democratic governance: the fragmentation of political parties, the commodification of electoral processes, the patrimonial character of elite coalitions, and the incomplete institutionalization of horizontal accountability mechanisms. The findings suggest that while Indonesia has achieved significant democratic milestones, its democracy remains substantively constrained by entrenched patronage networks, weak rule of law enforcement, and the unresolved tension between national cohesion and regional aspirations. This review contributes a conceptual framework for understanding Indonesian political stability and conflict as outcomes of negotiated power settlements among elite actors within a decentralized but still centralist-tending institutional architecture.